Successful endovascular treatment of extracranial arteriovenous malformation of a head: a case report - A. A. Sufianov; S. M. Karasev; R. R. Khafizov; R. R. Rustamov; R. A. Sufianov; E. S. Markin (Сеченовский вестник)
Introduction. Arteriovenous malformations (AVM) of the head represent the rare lesions that have a congenital, traumatic or post-infectious nature. In the last decade, endovascular methods have become the most prevalent in the treatment of AVM. Staged embolization is performed to achieve maximum eﬀect and minimize the complications.Case report. A 30-year-old female patient is presented with complaints of enlarged vessels in the frontal and parietal regions. CT-angiography scan and cerebral angiography showed extracranial AVM of the fronto-parietal regions with aﬀerent vascular supply from the right and left superﬁcial temporal and ophtalmic arteries with signiﬁcant expansion of the aﬀerent arteries and the presence of varix dilatation of the draining veins. Two-stage endovascular embolization of AVM was performed. The ﬁrst stage was embolization of the aﬀerent vessels from the left superﬁcial temporal artery system with exclusion of 60–65% AVM volume. Three months later, the second stage was performed with embolization of the afferent vessels from the right superﬁcial temporal artery system and the exclusion of 75–80% of the residual volume of AVM. The non-adhesive composition SQUIDR12 (Emboﬂu, Switzerland) and glue composition PHILR25% (Microvention, USA) were used. A good aesthetic eﬀect was achieved. Postoperative complications were not observed. There was no recurrence during the observation within a year.Summary. The staging and the use of various liquid embolization agents in the treatment of AVM of the head allow to achieve a good aesthetic outcome and prevent complications associated with facial soft tissue necrosis.